Allometric Scaling of a Metabolically Complex Camptothecin Analog - Ahlawat, Preeti; Srinivas, Nuggehally R (Arzneimittelforschung, 2009)
Allometry has been extensively used in the modern day drug development scenario to predict the human relevant parameters (clearance, CI, and volume of distribution at steady state, Vss) from animal data. The applicability of allometry in the prediction of human parameters for irinotecan (CAS 97682-44-5), an important topoisomerase I inhibitor, has been retrospectively investigated. Literature pharmacokinetic data has been gathered for both irinotecan and its main metabolite, SN-38 (CAS 86639-52-3), from several animal species. The corresponding human parameters were predicted using allometry (Cl and Vss for irinotecan; Cl/F for SN-38). Although irinotecan has a complex metabolism and disposition profile, it appeared that simple allometry predicted satisfactorily the human values for Cl (1.7648W0’669) and Vss (3.1277W0’9044) for irinotecan. On the contrary, Cl/F for SN-38 was over predicted by simple allometry (53.389W1’2773); and the applicability of bile correction factor rendered Cl/F of SN-38 to be closer to the observed human value (8.9641W1 3108). The investigation suggests that prospective allometric approaches may aid in the development of future compounds in this important pharmacological and chemical class of cytotoxics.
Keywords: Allometry; Camptothecin analog, clearance, pharmacokinetics, volume of distribution; CAS 7689-03-4; CAS 86639-52-3; CAS 97682-44-5; Irinotecan; SN-38; Toposiomerase I inhibitors